Investigating the challenges faced by bKash in implementing effective financial inclusion practices in Bangladesh - Chowdhury, Tasfia Tasnim (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.